2004
DOI: 10.1080/09286580490514513
|View full text |Cite
|
Sign up to set email alerts
|

The age- and gender-specific prevalences of refractive errors in Tehran: the Tehran Eye Study

Abstract: This report has provided details of the refractive status in the population. We have documented prevalences of myopia, hyperopia, astigmatism and anisometropia by age and gender, identifying more affected age- and gender-groups for prevention programs in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
99
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 21 publications
16
99
11
Order By: Relevance
“…8 It is difficult to compare the differences in refractive error found in this study with those found by previous authors due to varying definitions of refractive error, differences in the age groups, and varied techniques employed for the measurement of refractive error. But the prevalence of myopia is similar to that found in the Tehran Eye Study (21.8%), 9 and also in those over 15 years in Southern India (19.4%). 10 Where myopia is defined as a SE of greater than −1.0, the prevalence is lower than that reported in Sumatra (22.3%) 11 and in Singaporeans of Chinese descent (31.9%), 12 but equates with that reported in Australia (13%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…8 It is difficult to compare the differences in refractive error found in this study with those found by previous authors due to varying definitions of refractive error, differences in the age groups, and varied techniques employed for the measurement of refractive error. But the prevalence of myopia is similar to that found in the Tehran Eye Study (21.8%), 9 and also in those over 15 years in Southern India (19.4%). 10 Where myopia is defined as a SE of greater than −1.0, the prevalence is lower than that reported in Sumatra (22.3%) 11 and in Singaporeans of Chinese descent (31.9%), 12 but equates with that reported in Australia (13%).…”
Section: Discussionsupporting
confidence: 85%
“…11 Anisometropia increased significantly with age, a trend that has been demonstrated in previous studies. 9,11 In addition, we found that anisometropia was 8.3 (4.0-17.4; p < 0.001) times more common in those who were highly myopic (SE< −6.0). This adds to the morbidity associated with this condition and highlights the need for adequate refractive error correction in these people.…”
Section: Discussionmentioning
confidence: 77%
“…As study data on refraction were gathered before pupil dilation in subjects, it is possible that the prevalence of myopia is overestimated and hyperopia underestimated. 57 However, most of the current study population (61.6%) were aged over 50 years, and in this age-band, cycloplegic autorefraction is associated with a myopic shift and consequently an overestimation of myopia prevalence. 58 In conclusion, study authors revealed a protective association of UVAF-an objective marker of ocular outdoors light exposure and time spent outdoors-with myopia in this crosssectional study.…”
Section: Discussionmentioning
confidence: 78%
“…3,4,31 The prevalence of astigmatism is high in infancy (70% in the paper by Howland et al 31 ) with a significant decrease in older children (44.3% to 5.2% in 2-12 year-old children) 4 and then an increase with age: 41.4% in [16][17][18][19][20][21][22][23][24][25] year-old adults 5 and 37% in the 49-97 year-olds. 7 In our study, the prevalence increased from 36.5% for the youngest age group (5-15 years) to 81.2% for the oldest group (over 55 years old).…”
Section: Discussionmentioning
confidence: 98%